A SURVEY OF SENTIMENT ANALYSIS USING SENTIWORDNET ON BAHASA INDONESIA - Christina, Sherly; Ronaldo, Deddy (JURNAL TEKNOLOGI INFORMASI, 2018)
High internet usage in Indonesia brings a number of data user opinions. Useropinion data can be processed into information that is useful for decision making, datasearching and researching for production and marketing strategies. This researchconducted a survey on some Indonesian Sentiment Analysis research articles. Some of thesestudies have different topics and data sources, butuse Sentiwordnet as a lexical database.The results of this survey show the performance of Sentiwordnet can improve classificationaccuracy in the Sentiment analysis system for Indonesian text.